Teaching graphic design history - Heller, Steven 1950- (Allworth Press, an imprint of Skyhorse Publishing, 2019)
"Teaching the history of graphic design cannot simply be outlined by dates nor confined by places, but is defined by concepts and philosophies, as well as those who made, make, and inspire them. Teaching Graphic Design History is the first collection of essays, syllabi, and guides for conveying the heritage of this unique practice, from traditional chronologies to eclectic themes as developed by today's historians, designers, scholars, and documentarians"--
Keywords: Lehre; Grafikdesign; Geschichte; Graphic arts / History / Study and teaching (Higher); Graphic design (Typography) / History / Study and teaching (Higher); DESIGN / History & Criticism; DESIGN / General; DESIGN / Graphic Arts / General; EDUCATION / Teaching Methods & Materials / Arts & Humanities; Graphic arts / Study and teaching (Higher); History; Aufsatzsammlung